Interdisciplinary research of the neolithic Volga-Kama pottery - Vybornov, Aleksandr A. (Documenta Praehistorica, 2013)
In this article, we present a new method of studying Neolithic Volga-Kama pottery, which involves typological and technological analysis and the radiocarbon dating of vessels. As a result of the research, areas with Early Neolithic Volga-Kama pottery traditions are presented.
Keywords: arheološka najdišča; ceramic; Kama; keramika; lončarstvo; neolitik; Rusija